Detecting hidden diets and disease: Zoonotic parasites and fish consumption in Mesolithic Ireland. (September 2018) - Perri, Angela R.; Power, Robert C.; Stuijts, Ingelise; Heinrich, Susann; Talamo, Sahra; Hamilton-Dyer, Sheila; Roberts, Charlotte
Abstract: Archaeoparasitology is increasingly being used as a tool in archaeological research to investigate relationships between past humans, environments, diets and disease. It can be particularly useful in contexts where parasite eggs preserve, but human and faunal remains do not, including in the identification of disease and/or dietary items otherwise absent from the local archaeological record. We analyzed soil samples from the Late Mesolithic layers of the lake island site of Derragh in County Longford, Ireland. All samples were positive for the presence of Diphyllobothrium sp., an intestinal fish tapeworm that infects humans, causing diphyllobothriasis. Though fish are thought to be a staple food in Mesolithic Ireland, evidence for fishing and subsistence from this period is extremely fragmentary. Similarly, there is little available evidence for disease, primarily due to the lack of human remains. This finding represents the earliest known presence of human-derived parasites in Ireland, the earliest known finding of Diphyllobothrium sp. in Europe and the only finding of the tapeworm from hunter-gatherer contexts. It suggests parasitic infections, particularly those resulting from undercooked food, may be more common in ancient hunter-gatherer populations than previously suspected. The presence of these zoonotic parasites at hunter-gatherer sites can provide important insight into local environments, health and disease, and culinary practices. In locations like Mesolithic Ireland, the presence of parasites may assist in the identification of subsistence activities, such as fishing, and specific prey.